2014
DOI: 10.1103/physreve.89.023207
|View full text |Cite
|
Sign up to set email alerts
|

Topological properties of microwave magnetoelectric fields

Abstract: Collective excitations of electron spins in a ferromagnetic sample dominated by the magnetic dipole-dipole interaction strongly influence the field structure of microwave radiation. A small quasi-two-dimensional ferrite disk with magnetic-dipolar-mode (MDM) oscillation spectra can behave as a source of specific fields in vacuum, termed magnetoelectric (ME) fields. A coupling between the time-varying electric and magnetic fields in the ME-field structures is different from such a coupling in regular electromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…These specific near fields -the ME fields -give evidence for spontaneous symmetry breakings at the resonant states of MDM oscillations. This symmetry breaking is characterized by the helicity parameter [13,15,52]. The ME-field singularity is strongly related to edge chiral currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific near fields -the ME fields -give evidence for spontaneous symmetry breakings at the resonant states of MDM oscillations. This symmetry breaking is characterized by the helicity parameter [13,15,52]. The ME-field singularity is strongly related to edge chiral currents.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies [13,15,40,52], it was shown that topology of the near fields originated from a MDM ferrite disk -the ME fields -is characterized both by the power-flow vortices and the helicity parameters. While the power transmission in a two-port microwave structure is strongly related to the power-flow vortices of the twisting excitations, the helicity characteristics of these excitations (being local characteristics of the field geometry) are very slightly correlated with the power transmission effect.…”
Section: B Chiral Edge Electric Currentsmentioning
confidence: 99%
“…In a structure of a thin rectangular waveguide with an embedded quasi-2D ferrite disk [36], the contact regions can be considered as two vacuum cylinders with the same diameter as a ferrite disk. This model is inapplicable in a case of a "thick" microwave waveguide [82,83]. However, use of two dielectric cylinders with a high dielectric constant allows considering these cylinders as the contact regions in a "thick" microwave waveguide.…”
Section: Mdm Resonances and Bound States In The Microwave Continuummentioning
confidence: 99%
“…Because of rotations of localized field configurations in a fixed observer inertial frame, the linking between the EM and ME fields cause violation of the Lorentz symmetry of spacetime. In such a sense, ME fields can be considered as Lorentz-violating extension of the Maxwell equations [5,6].…”
Section: Disksmentioning
confidence: 99%
“…To characterize the ME-field singularities, the helicity (chirality) parameter was introduced. A time average helicity parameter for the near fields of a ferrite disk with MDM oscillations is defined as [5,6,14]:…”
Section: Disksmentioning
confidence: 99%